Extracellular vesicles of human diabetic retinopathy retinal tissue and urine of diabetic retinopathy patients are enriched for the junction plakoglo bin protein - Mighty, Jason; Rubio-Navarro, Alfonso; Shi, Cui; Zhou, Jing; Flores-Bellver, Miguel; Heissel, Søren; Onwumere, Onyekwere; Einbond, Linda; Gharbaran, Rajendra; Casper, Daniel S.; Benito-Martin, Alberto; Redenti, Stephen (Frontiers in Endocrinology, 2023)
Diabetic Retinopathy (DR) is a potentially blinding retinal disorder that develops through the pathogenesis of diabetes. The lack of disease predictors implies a poor prognosis with frequent irreversible retinal damage and vision loss. Extracellular Vesicles (EVs) present a novel opportunity for pre-symptomatic disease diagnosis and prognosis, both severely limited in DR. All biological fluids contain EVs, which are currently being studied as disease biomarkers. EV proteins derived from urine have emerged as potential noninvasive biomarkers. In this study, we isolated EVs from DR retinal tissue explants and from DR patients’ urine, and characterized the vesicles, finding differences in particle number and size. Next, we performed proteomic analysis on human explanted DR retinal tissue conditioned media, DR retinal EVs and DR urinary EVs and compared to normal human retinal tissue, retinal EVs, and urinary EVs, respectively. Our system biology analysis of DR tissue and EV expression profiles revealed biological pathways related to cell-to-cell junctions, vesicle biology, and degranulation processes. Junction Plakoglobin (JUP), detected in DR tissue-derived EVs and DR urinary EVs, but not in controls, was revealed to be a central node in many identified pathogenic pathways. Proteomic results were validated by western blot. Urinary EVs obtained from healthy donors and diabetic patient without DR did not contain JUP. The absence of JUP in healthy urinary EVs provide the basis for development of a novel Diabetic Retinopathy biomarker, potentially facilitating diagnosis.